How emotions and green altruism explain consumer purchase intention toward circular economy products: A multi‐group analysis on willingness to be environmentally friendly - Chao, Cheng‐Min; Yu, Tai‐Kuei (Business strategy and the environment, 2024)
Circular economy products are one of the solutions that can help solve the current environmental crisis and consequently achieve environmental sustainability. The theory of planned behavior (TPB) is the most important social psychological theory to explain individual purchasing behavior. However, the theory lacks a consideration of emotions, green altruism, and other factors. In order to address the research gap, this study proposes and tests a new theoretical model that incorporates variables such as emotions, green altruism, and the willingness to be environmentally friendly (WEF) into its extended model based on the TPB framework, in order to investigate the determinants that have an effect on Taiwanese consumers' purchase intention toward circular economy products. This study also uses multi‐group analysis (MGA) to analyze the moderating effects of WEF on its new theoretical model. It collected data from 387 Taiwanese consumers and analyzed the data using partial least squares (PLS). The research results showed (1) emotions, attitudes, green altruism, and perceived behavior control have a positive effect on consumer purchase intention toward circular economy products; (2) emotions have a positive effect on attitudes, green altruism, subjective norms, and perceived behavior control; and (3) groups with different levels of WEF have significant differences on consumer purchase intention toward circular economy products, in terms of emotions, attitudes, and green altruism. The results of this study can provide a reference for manufacturers and public policy makers to understand how consumers' emotions and green altruism can affect the decision‐making process to making purchase of circular economy products.